PS02.221: THE SUCCESSFUL CONSERVATIVE MANAGEMENT OF CHYLOTHORAX WITH ETILEFRINE AND SOMATOSTACHIN ANALOG AFTER ESOPHAGECTOMY: A CASE REPORT AND REVIEW OF THE LITERATURE. (14th September 2018) - Yoshino, Yutaro; Nakazato, Hidetsugu; Tomiyama, Takeshi; Nagamine, Shinji; Tomori, Takehiko; Inamine, Susumu; Miyagi, Jun; Nagayoshi, Seiji; Omine, Yasushi; Miyara, Tetsuhiro
Abstract: Background: Chylothorax is a severe complication after esophagectomy and is sometimes difficult to treat. Patients are treated with surgical and conservative therapies, including nutritional management. Methods: Case: The patient was an 80-year-old man who had complained of dysphagia. Upper gastrointestinal endoscopy demonstrated a Borrmann type 2 tumor in the lower esophagus. Biopsy revealed squamous cell carcinoma. He was referred to our hospital after radiotherapy (40 Gy). The clinical stage, according to the UICC 7th edition, was cT3N1M0 cStage IIIA. Transthoracic esophagectomy with 2-field lymph node dissection was performed. The thoracic duct was observed. The postoperative chylothorax volume was < 1000 ml/day and required continuous drainage management. Results: The single use of somatostatin analog failed to reduce the patient's chylothorax. Treatment with etilefrine and somatostachin analog led to the resolution of the patient's chylothorax. Conclusion: The management of chylothorax with etilefrine and somatostachin analog may be a treatment option for patients with a low chylothorax volume or elderly patients. Disclosure: All authors have declared no conflicts of interest.